Resiliensi Remaja Ditinjau dari Orangtuanya yang Bekerja sebagai TKI dan Bukan TKI - Maulinia Lestari; Ratna Dyah Suryaratri; Zarina Akbar (Universitas Kristen Maranatha, 2021)
This study aims to determine the differences in resilience between adolescent students whose parents work as migrant workers and those who are non-migrant workers in Indramayu, West Java. This research was conducted using a comparative descriptive method with a quantitative approach. There were 150 respondents aged 15-17 years consisting of 75 adolescent students with TKI parents and 75 adolescent students with non-TKI parents. The resilience was measured using the Connor-Davidson Resilience Scale (CD-RISC). The result shows a significant difference of resilience, where the resilience level of adolescents with non-TKI parents is higher than adolescents with parents who work as migrant workers. An important implication of this research is the need for a psychoeducational program for adolescents with parents of migrant workers in synergy with the school in order to increase the resilience of these adolescents in dealing with pressures and problems both at home, at school and in social life. Keywords: teenagers, migrant workers’ parents, non-migrant workers’ parents, resilience; Indramayu